2019
DOI: 10.1186/s42408-019-0048-6
|View full text |Cite
|
Sign up to set email alerts
|

Empowering strategic decision-making for wildfire management: avoiding the fear trap and creating a resilient landscape

Abstract: In recent years, fire services in Mediterranean Europe have been overwhelmed by extreme wildfire behavior. As a consequence, fire management has moved to defensive strategies with a focus only on the known risks (the fear trap). In this region, wildfires can change rapidly, increasing the uncertainty and causing complex operational scenarios that impact society right from the initial hours. To address this challenge, proactive approaches are an alternative to defensive and reactive strategies. We propose a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 24 publications
1
66
0
3
Order By: Relevance
“…On the other hand, it has been proposed that successfully controlling all small fires has positively contributed to the fuel build‐up increase problem in Mediterranean landscapes during the last decades (Otero & Nielsen, 2017). In this sense, it is worth noting that managing large fire‐prone areas requires an integrative perspective including the creation of fire‐adapted human communities, the generation of resilient landscapes, and the prevention of human‐induced undesired fire inception in addition to a safe and efficient wildfire response (Alcasena et al., 2019; Castellnou et al., 2019; Dunn et al., 2020). Still, a safe and efficient response is a core goal of wildfire management in Mediterranean areas where numerous smallholdings and disperse communities intermingle with poorly managed forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been proposed that successfully controlling all small fires has positively contributed to the fuel build‐up increase problem in Mediterranean landscapes during the last decades (Otero & Nielsen, 2017). In this sense, it is worth noting that managing large fire‐prone areas requires an integrative perspective including the creation of fire‐adapted human communities, the generation of resilient landscapes, and the prevention of human‐induced undesired fire inception in addition to a safe and efficient wildfire response (Alcasena et al., 2019; Castellnou et al., 2019; Dunn et al., 2020). Still, a safe and efficient response is a core goal of wildfire management in Mediterranean areas where numerous smallholdings and disperse communities intermingle with poorly managed forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is the cornerstone of the methodology presented. It is a usual simplification taken both by researchers and firefighters [12,13,[17][18][19]22]. Although fire and landscape are naturally seen as a continuous phenomenon, preventive actions used to be taken within finite set of possible places and a network is an appropriate framework for these decisions.…”
Section: Fire Probabilitymentioning
confidence: 99%
“…In a recent study, Ref. [18] presents a methodology used by Catalan Fire and Rescue Service based on modelling landscape with a network. A case study of Odena (Spain) is shown where the landscape is divided into 23 sectors ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…As the complexity of wildland fire management has increased, so too has the need for risk-based decision support designed to enhance the safety and effectiveness of large fire management [17][18][19][20][21][22][23][24][25][26][27][28]. In recent years, the fire science community has developed a wide range of operationally focused assessment and planning tools.…”
Section: Introductionmentioning
confidence: 99%